2020
DOI: 10.1016/j.livsci.2020.104222
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of cow milk yield and pre-weaning calf growth response in temperate pasture-based beef suckler systems: A meta-analysis

Abstract: Quantification of cow milk yield and pre-weaning calf growth response in temperate pasture-based beef suckler systems: A meta-analysis, Livestock Science (2020), doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 60 publications
(79 reference statements)
0
7
0
Order By: Relevance
“…Throughout development, calves increase the demand for milk (Sapkota et al, 2020). With greater demand for milk production by the mammary gland, the female enters into a negative energy balance that can be alleviated with better nutritional support (Ayres et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout development, calves increase the demand for milk (Sapkota et al, 2020). With greater demand for milk production by the mammary gland, the female enters into a negative energy balance that can be alleviated with better nutritional support (Ayres et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in preovulatory follicle size in 80 days C‐TAI cows can be related to the high demand for milk by the calf, as they are lactating cows. Throughout development, calves increase the demand for milk (Sapkota et al, 2020). With greater demand for milk production by the mammary gland, the female enters into a negative energy balance that can be alleviated with better nutritional support (Ayres et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…McGee et al (1998) showed that primiparous suckler cows offered grass silage supplemented with 2 kg of concentrates daily postpartum had less weight loss and greater milk yield resulting in greater early life calf growth than those offered only grass silage. Milk, a primary source of nutrients for the suckled calf in early postnatal life, remains a significant component of the diet until weaning, and thus, is a primary driver of calf pre-weaning growth (Sapkota et al, 2020). Early turnout to pasture in spring increases grazed grass in the annual diet of the cow.…”
Section: Suckler Cow Nutritionmentioning
confidence: 99%
“…Different mathematical models have been used to characterise milk yield in dairy cows, from traditional models describing the shape of the lactation curve to individually adjusted polynomial curves based on well-established statistical models (Harder et al, 2019). Fewer modelling studies have been conducted on beef cattle because it is not routinely measured in common practice (Cortés-Lacruz et al, 2017;Sepchat et al, 2017;Sapkota et al, 2020). Animal performance can be affected by perturbations caused by climate, management or diseases, which can compromise both animal nutrition and welfare.…”
Section: Response Curvesmentioning
confidence: 99%